Synthesis, characterization and inclusion into liposomes of a new cationic pyrenyl amphiphile. (October 2016) - Petaccia, Manuela; Giansanti, Luisa; Leonelli, Francesca; Bella, Angela La; Gradella Villalva, Denise; Mancini, Giovanna
Graphical abstract: Highlights: A new fluorescent amphiphile was prepared and characterized. Mixed liposomes containing DOPC at different molar ratio were also investigated. Lipid organization and excimer/monomer ratio vary as a function of liposomes composition. Abstract: The aggregation properties of a new cationic fluorescent amphiphile tagged on the hydrophobic tail with a pyrene moiety and bearing two hydroxyethyl functionalities on the polar headgroup were investigated by fluorescence experiments as pure components or in mixed liposomes containing an unsaturated phospholipid, 1, 2‐dioleoyl- sn -glycero-3-phosphocholine, at different molar ratios. The obtained results put in evidence that the conformation and the miscibility of the lipids in the aggregates strongly influence the excimer/monomer ratio. Mixed monolayers at the same composition were investigated by Langmuir compression isotherms to deepen the understanding of lipid organization and miscibility, both in the polar and in the hydrophobic regions. The presence of two hydroxyethyl functionalities on the polar headgroup of the newly synthesized amphiphile exerts a shielding effect of the charge of the amphiphile increasing the compressibility of lipid components in contrast with the disturbing effect of the unsaturated acyl chains of the phospholipid.